PENGARUH RASIO KEUANGAN, STRUKTUR KEPEMILIKAN, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN DI INDONESIA - Jessie Indradjaja; Maria (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to analyze and obtain an empirical evidence about the influence of financial ratio, ownership structure, and other factors on firm value in Indonesia. The variables used on this study are profitability, leverage, liquidity, institutional ownership, managerial ownership, asset growth, firm size, dividend policy, and board of independent commissioners as independent variables and firm value as dependent variable. The samplet used in this research are non-financial companies listed in Indonesian Stock Exchange (IDX) during period 2017-2020. The method used in sample selection in this study is purposive sampling method and there are 51 companies selected as final samples. In this study, the hypothesis is tested by using multiple regression analysis. The result of this research shows that profitability, leverage, firm size, and board of independent commissioners have influence on firm value because the higher profitability will attract investors, the higher of the solvability, the firm will have more longer durability, the higher of the firm size mean have more assets, the higher of the independent board of commissioners, the company's management supervision will be better. While other variables such as liquidity, institutional ownership, managerial ownership, asset growth, and dividend policy, have no influence on firm value.